(untitled) (Polish Yearbook of International Law, 2016)
This article attempts to discover the key elements of the democratic principle, as described by the judges sitting in Luxembourg and Strasbourg, whose case law reveals the underlying idea of democracy at the supranational level. Until recently the debate on democracy was limited to the national level. But things are changing, and this article shows the gradual emergence of a process led by supranational courts, in which the application of the democratic principle finds multiple grades and variations. In this way the supranational/international courts have opened a new chapter in the process of constitutionalization of international law.